Excess particulate organic matter negatively affects the ecophysiology of the widespread soft coral Xenia umbellata - Claudia E L Hill; Julia Rücker; Nele Eichhorn; Selma D Mezger; Giulia Caporale; Yusuf C El-Khaled; Sahara Blanco; Christian Wild; Arjen Tilstra (PANGAEA, 2025)
Coastal coral reefs are experiencing rising concentrations of organic matter. While dissolved organic matter (DOM), rather than particulate organic matter (POM), may negatively impact hard corals, the impact on soft corals remains unclear. We examined the physiological effect of 20 mg L-1 of organic carbon (C) addition on the widespread Indo-Pacific soft coral Xenia umbellata in a series of tank experiments over 28 days. We supplied DOM as glucose, and two POM sources as phytoplankton (2 - 5 μm length) and zooplankton (150 – 200 μm length). We comparatively assessed coral morphology, pulsation, colouration, algal symbiont densities, chlorophyll a, oxygen fluxes, and mortality. Corals in the control and DOM enrichment treatments exhibited no morphological or physiological changes, whereas, excess phyto- and zooplankton caused disfigurement of the polyp tentacles and shortening of its pinnules. This coincided with a mortality of 11 and 14%, respectively, a 35% reduction in pulsation rates, and darkening of the polyps (with excess zooplankton), while other assessed response variables remained stable. This suggests that in contrast to many hard corals, the soft coral X. umbellata is vulnerable to excess POM rather than DOM, with amplified effects upon exposure to larger particles. Our results suggest that excess POM may damage the delicate feeding apparatus of X. umbellata, thereby reducing pulsation and lowering gas exchange. In turn, this can cause nutritional, and ultimately, energy deficiencies by directly affecting heterotrophic and autotrophic feeding. Our findings indicate that the global-change-resilient soft coral X. umbellata is vulnerable to local eutrophication, particularly high concentrations of POM. Xenia umbellata originates from the Red Sea.